1999
DOI: 10.1007/s005860050147
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of spinal cord compression related to misplaced pedicle screws in thoracic scoliosis

Abstract: Utilization of thoracic pedicle screws is controversial, especially in the treatment of scoliosis. We present a case of a 15-year-old girl seen 6 months after her initial surgery for scoliosis done elsewhere. She complained of persistent epigastric pain, tremor of the right foot at rest, and abnormal feelings in her legs. Clinical examination revealed mild weakness in the right lower extremity, a loss of thermoalgic discrimination, and a forward imbalance. A CT scan revealed at T8 and T10 that the right pedicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(70 citation statements)
references
References 20 publications
0
65
1
2
Order By: Relevance
“…Both reported excellent correction using such techniques (72% of Cobb angle correction for Suk and 59% for Liljenqvist). However, this can only be used in experienced hands and the possible neurologic complications due to a misplaced pedicle screw must be kept in mind [20]. The small size, the rotation and the surgical anatomy of the pedicle at the thoracic level in AIS makes the insertion of pedicle screws even more difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both reported excellent correction using such techniques (72% of Cobb angle correction for Suk and 59% for Liljenqvist). However, this can only be used in experienced hands and the possible neurologic complications due to a misplaced pedicle screw must be kept in mind [20]. The small size, the rotation and the surgical anatomy of the pedicle at the thoracic level in AIS makes the insertion of pedicle screws even more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Their superior correction could be explained by the rigid fixation achieved with pedicle fixation and the number of vertebrae instrumented. However, neurologic concern still remains with the use of pedicle screws [20]. Specialized pedicle hooks (SPH), where the pedicle hooks are augmented with 3.2-mm fixation screws were devised as an alternative to pedicle screws in the thoracic spine (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In thoracic scoliosis, Suk et al demonstrated a shorter fusion length and a better three-dimensional correction with posterior pedicle screw instrumentation compared to hooks [39]. However, both neural and vascular, as well as visceral, structures are at potential risk from misplaced pedicle screws [6,10,16,35,[40][41][42]. In order to evaluate frontal and sagittal plane correction in thoracolumbar and lumbar scoliosis by use of segmental pedicle screw instrumentation, with special regard to fusion length and accuracy of pedicle screw placement, a prospective clinical trial was conducted.…”
Section: H Halm T Niemeyer T Link U Liljenqvistmentioning
confidence: 99%
“…Several studies have been devoted to developing safe techniques for screw placement [3,5,8,9], whereas others focus on anatomic structures at risk during screw placement [5, 7, 12, 16, 19-22, 29, 30, 32, 33]. Although rare, neurologic injury as a result of malpositioned pedicle screws has been reported [4,6,18,23]. When postoperative neurologic changes occur, it is vital that the surgeon have a reliable method to image the spine to look for iatrogenic injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, use of pedicle screws involves some risk, especially if the pedicle wall is violated or the screw tip extends anywhere outside the vertebral body. Numerous authors reported misplaced screws with resultant nerve root compression, impingement on vascular structures, or spinal cord injury [4,6,13,23]. In situations where postoperative imaging is required to assess implant position, several options exist, including plain radiography, CT, and MRI.…”
Section: Introductionmentioning
confidence: 99%